A clinical approach to the successful management of variations of middle mesial canals: A case series - Raghavendra Penukonda; Prahlad A Saraf; Thimmanagowda N Patil; Sneha S Vanaki (Wolters Kluwer Medknow Publications, 2018)
The possible variations of anatomical and morphological characteristics of the teeth are very important especially for the endodontic practitioners for successful treatment. Mandibular molars are most commonly affected by dental caries and require endodontic treatment. Mandibular molars exhibit variations in its internal anatomy; one among those is the presence of an extra canal in the mesial root called as middle mesial (MM) canal. Detection of these minute canals requires a proper clinical knowledge and radiographic examination. This article presents the treatment of three cases of mandibular first molars with MM canals without the aid of any magnification devices.